Unfolding: how to build belonging - Pedroni, Fabiana (Farol, 2023)
This text defends the principle of splitting between theoretical research and poetic research as part of the processes of building belonging. In this sense, I establish relationships between ideas from Boaventura de Souza Santos, Ailton Krenak and Daniel Munduruku and the Heideggerian sense of dwelling. Initially, I narrate theoretical-poetic processes that point to the constructive need, linked to everyday life, and the creation of memories as fundamental to inhabiting the world. From these theoretical-poetic experiences, I point to the urgency of belonging as a reaction to the permanent crisis, highlighted by climate chaos and the COVID-19 pandemic.
Keywords: poetic processes; build; inhabit; belong; unfold